2011
DOI: 10.1016/j.jmoldx.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Metastasis Inducer S100A4 Transcripts in Plasma of Colon, Rectal, and Gastric Cancer Patients

Abstract: Early detection of tumors and metastases is critical for improving treatment strategies and patient outcomes.The development of molecular markers and simple tests that are clinically applicable for detection, prognostication, and therapy monitoring is strongly needed. The gene S100A4 has long been known to act as a metastasis inducer. High S100A4 levels in the primary tumor are prognostic for metachronous metastasis and correlate with reduced patient survival. We provide, for the first time, a plasma-based ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 57 publications
2
52
1
Order By: Relevance
“…For cancer patients, high mRNA and protein levels of S100A4 have shown to correlate with decreased overall and disease-free survival. Overexpression is correlated with aggressive tumor growth and formation of metastasis [88][89][90][91]. S100A4 is a transcriptional target of β-catenin [88].…”
Section: Wnt Signaling Target: S100a4mentioning
confidence: 99%
See 1 more Smart Citation
“…For cancer patients, high mRNA and protein levels of S100A4 have shown to correlate with decreased overall and disease-free survival. Overexpression is correlated with aggressive tumor growth and formation of metastasis [88][89][90][91]. S100A4 is a transcriptional target of β-catenin [88].…”
Section: Wnt Signaling Target: S100a4mentioning
confidence: 99%
“…Overexpression is correlated with aggressive tumor growth and formation of metastasis [88][89][90][91]. S100A4 is a transcriptional target of β-catenin [88]. It is located in the cytoplasm, the nucleus, and the extracellular space.…”
Section: Wnt Signaling Target: S100a4mentioning
confidence: 99%
“…On the basis of the available literature, where S100A4 was investigated either in the serum (51 studies; two of them in a relation to a gastroenterology disorderliver fibrosis and cirrhosis (44,45)) or in plasma samples (26 studies; two of them were accomplished in gastric and colorectal cancer (46,47)), we decided to investigate serum S100A4. All individuals enrolled into our study including all healthy controls and all IBD patients were investigated in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…In China, there are approximately 160,000 deaths from gastric cancer annually (Chen et al, 2004). A number of studies have reported the relationship between S100A4 expression and the prognosis of gastric cancer (Yonemura et al, 2000;Yu et al, 2006;Huang et al, 2008;Wang et al, 2010;Feng et al, 2011;Stein et al, 2011;Zhao et al, 2013;Li et al, 2013) However, the association of S100A4 with gastric prognosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies identified 16 members of this family, based on amino acid sequence homology and similar structural properties (Schafer and Heizmann, 1996). S100A4 is highly expressed in many cancers (Kikuchi et al, 2006;Ai et al, 2008;Kwak et al, 2010) and its presence predicts a poor outcome, such as in pancreatic cancer, (Ai et al 2008), colorectal cancer (Kwak et al, 2010), ovarian carcinoma (Kikuchi et al, 2006), bladder carcinoma (Yao et al 2007), esophageal carcinoma (Ji et al, 2004), and gastric carcinoma (Yonemura et al, 2000;Yu et al, 2006;Huang et al, 2008;Feng et al, 2011;Wang et al, 2010;Stein et al, 2011;Zhao et al, 2013;Li et al, 2013). However, the prognostic value of S100A4 in patients with gastric cancer is still controversial.…”
Section: Introductionmentioning
confidence: 99%